FAKTOR-FAKTOR YANG MEMPENGARUHI LOYALITAS KONSUMEN GENERASI MILENIAL TERHADAP E-MARKETPLACE - Made Mas Sujana Wirakusuma; William Agung Kandiawan; Jean Raymond Runtu; Evelyn Hendriana (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Previous research on customer loyalty in e-marketplaces mostly relates it to service quality, satisfaction, and trust. Meanwhile, e-marketplace consumers also need effective service recovery and a pleasant customer experience, especially for millennial consumers. However, research on the factors that shape loyalty to e-marketplaces in Indonesia, especially on the millennial generation, rarely sees the relationships simultaneously. This study aims to examine the effect of consumer experience, service quality, and service recovery on consumer loyalty through consumer satisfaction and trust toward online marketplace. Data were obtained from 169 millennial consumers of Tokopedia, Shopee, and Bukalapak di Greater Jakarta selected using purposive sampling technique. The hypotheses were tested using partial least square structural equation modelling (PLS-SEM) technique. This study found that consumer experience and service quality had a positive effect on customer satisfaction. Meanwhile, service quality and service recovery had a positive effect on customer trust. Since the study involves respondents who had experienced problems when shopping in online marketplaces, customer satisfaction did not directly affect loyalty, but must be through customer trust.